POLITIK HUKUM TINDAK PIDANA KORPORASI DI INDONESIA: ERA KUHP LAMA VERSUS KUHP BARU - Reni Okpirianti; Nur Husni Emilson; Fadiah Adilah Kusmayadi; Nabila Tsabitah; Marsya Ika R (The Juris, 2026)
Economic globalization and market liberalization not only open up space for business growth, but also give birth to new forms of crime in the economic sector. In international practice, the recognition of corporations as subjects of criminal law has been going on for a long time: in the United States. Indonesia began to recognize corporations as perpetrators of criminal acts since the Emergency Law of 1951 and especially Law No. 7 Drt 1955 concerning Economic Crimes. However, in law enforcement practices, especially in the old Criminal Code (KUHP) regime, perpetrators of criminal acts still focus on individuals. This often causes problems in the preparation of indictments when criminal acts involve corporations. The research method used in this study is normative. The research findings show that the most fundamental change in the legal policy of corporate crime in Indonesia is the transition from the old Criminal Code (KUHP), which did not recognize corporations as legal subjects, to the new Criminal Code (Law No. 1 of 2023), which explicitly establishes corporations as perpetrators of criminal acts. Thus, the New Criminal Code can be seen not merely as a replacement for the Old Criminal Code, but as an important milestone in the renewal of the national criminal law system that is progressive, adaptive, fair, and relevant to current and future global challenges. The success of this transformation depends heavily on careful implementation, the preparation of comprehensive implementing regulations, and ongoing supervision.